2010
DOI: 10.1093/nar/gkq1003
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CD44 3′-untranslated region regulates endogenous microRNA functions in tumorigenesis and angiogenesis

Abstract: The non-coding 3′-untranslated region (UTR) plays an important role in the regulation of microRNA (miRNA) functions, since it can bind and inactivate multiple miRNAs. Here, we show the 3′-UTR of CD44 is able to antagonize cytoplasmic miRNAs, and result in the increased translation of CD44 and downstream target mRNA, CDC42. A series of cell function assays in the human breast cancer cell line, MT-1, have shown that the CD44 3′-UTR inhibits proliferation, colony formation and tumor growth. Furthermore, it modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
166
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(168 citation statements)
references
References 38 publications
1
166
0
1
Order By: Relevance
“…We have previously demonstrated that expression of the CD44 39 UTR inhibited tumor growth and angiogenesis, which upregulated CD44 and CDC42 expression by binding to the miRNAs miR-216a, miR-330 and miR-608 (Jeyapalan et al, 2011). We hypothesize that the CD44 39 UTR can also regulate the expression of many other proteins because a 39 UTR has the capacity to bind many miRNAs, which can affect other mRNAs downstream.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We have previously demonstrated that expression of the CD44 39 UTR inhibited tumor growth and angiogenesis, which upregulated CD44 and CDC42 expression by binding to the miRNAs miR-216a, miR-330 and miR-608 (Jeyapalan et al, 2011). We hypothesize that the CD44 39 UTR can also regulate the expression of many other proteins because a 39 UTR has the capacity to bind many miRNAs, which can affect other mRNAs downstream.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, miRNAs can be degraded through binding with the 39 UTR, which will protect target mRNAs from translational inhibition. Previously, we demonstrated that a noncoding transcript, CD44 39 UTR, was able to antagonize miRNAs involved in cell cycle regulation, which resulted in an increase in CDC42, a cell cycle regulator, to result in decreased tumorigenesis in the breast cancer cell line MT1 (Jeyapalan et al, 2011). Additionally, the CD44 39 UTR was found to increase endothelial cell activities and angiogenesis in vivo.…”
Section: Introductionmentioning
confidence: 95%
“…For instances, the 3′ UTR of CD44 can be combined by miR-216a, miR-330 and miR-608 to affect the expression of CDC42, thereby regulating the proliferation, apoptosis and angiogenesis phenotype of human breast cancer cell line MT-1 [53]. These studies suggest that miRNAs might also have functional relationships in vascular remodeling.…”
Section: Mirnas In Vascular Injury and Remodeling-related Diseasementioning
confidence: 97%
“…Most miRNAs bind and target the 39-untranslated region (39UTR) of mRNAs with imperfect complementarity and function as translational repressors. Conversely, it has been demonstrated that the 39UTR and other non-coding RNAs can regulate miRNA functions (Jeyapalan et al, 2011;Lee et al, 2009;Lee et al, 2011). This newly discovered class of regulatory molecules has been demonstrated to exert diverse biological functions in regulating cell activities such as cell proliferation Viticchiè et al, 2011;Yu et al, 2012), cell differentiation (Goljanek-Whysall et al, 2012;Guo et al, 2012;Kahai et al, 2009), apoptosis , morphogenesis (Wang et al, 2008a), invasion Luo et al, 2012), tissue growth (Shan et al, 2009), tumor formation (Nohata et al, 2012;Volinia et al, 2006), angiogenesis Smits et al, 2010;Zou et al, 2012), and metastasis (Huang et al, 2008;Ma et al, 2007;Rutnam and Yang, 2012a).…”
Section: Introductionmentioning
confidence: 99%